Imaging Findings of 3-Dimensional Bioabsorbable Breast Implant Device - Patel , M.; Kapoor , M.; Scoggins , M. (Seram, 2021)
Background Information: The BioZorb® (Focal Therapeutics, Aliso Viejo, California) is a 3-dimensional bioabsorbable device used to mark the surgical resection cavity after breast conservation surgery. The device incorporates six titanium clips to assist in demarcating the surgical bed for postoperative radiation treatment planning. As surgeons and radiation oncologists increasingly use this device in their clinical practice, it is important for radiologists to become familiar with its expected imaging appearance on multiple modalities. While the effectiveness of the BioZorb® device has been analyzed from the radiation oncology perspective, there are few articles presenting multimodality imaging findings in both normal and abnormal cases. Educational Goals/Teaching Points: The goal of this exhibit is to demonstrate the expected appearance and normal evolution of the BioZorb® device on postoperative mammographic, sonographic, MRI, CT, and radiographic images, and to demonstrate the multimodality appearance of recurrence involving the device after breast conservation surgery. Key Anatomic/Physiologic Issues and Imaging Findings/Techniques: The six titanium clips of the BioZorb® device are radio-opaque and therefore easily recognized on mammography, chest radiography and CT examination based on their unique configuration. Initial post-surgical baseline mammography demonstrates well-spaced titanium clips in a well-circumscribed, oval, equal density mass. Over the course of follow-up, the expected evolution of findings on mammography is a decrease in size of the oval mass with less space noted between the titanium marker clips. Similar associated findings are identified sonographically, with the initial postoperative ultrasound demonstrating an oval area of shadowing at the scar associated with BioZorb® device, which subsequently decreases in size and begins to demonstrate an isoechoic appearance. Susceptibility artifact related to the device is well seen on T1-weighted MR images with no suspicious associated enhancement in a benign post-operative case. Imaging findings of recurrence at the surgical site include focal increased density associated with the BioZorb® with correlating suspicious mass demonstrating irregularity and increased vascularity sonographically, along with correlating suspicious enhancement on post-contrast T1-weighted MR imaging. Conclusion: As the treatment of breast cancer requires a multi-team approach, it is important to be well-versed in normal and abnormal imaging findings associated with the latest devices being implanted in patients undergoing breast conservation surgery.